The Cultural Politics of Anti-Elitism - Ege, Moritz; Springer, Johannes (Taylor & Francis, 2023)
This book examines the highly ambivalent implications and effects of anti-elitism. It draws on this theme as a cross-cutting entry point to provide transdisciplinary analysis of current conjunctures and their contradictions, drawing on examples from popular culture and media, politics, fashion, labour and spatial arrangements. Using the toolboxes of media and discourse analysis, hegemony theory, ethnography, critical social psychology and cultural studies more broadly, the book surveys and theorizes the forms, the implications and the ambiguities and limits of anti-elitist formations in different parts of the world. Anti-elitist sentiments colour the contemporary political conjuncture as much as they shape pop cultural and media trends. Populists, right-wing authoritarian ones and others, direct their anger at cultural, political and, sometimes, economic elites while supporting other elites and creating new ones. At the same time, ""elitist"" knowledge and expertise, decision-making power and taste regimes are being questioned in societal transformations that are discussed much more positively under headlines such as participation or democratization. The book brings together a group of international, interdisciplinary case studies in order to better understand the ways in which the battle cry ""against the elites"" shapes current conjunctures and possible future politics, focusing on themes such as nationalist political discourse in India, Austria, the UK and Hungary, labour struggles and anti-oligarchy rhetoric in Russia, tax-avoiding elites and fiscal imaginaries, working-class agency, Melania Trump as a celebrity narrative in Slovenia, aesthetic codes of the Alt-Right, football hooliganism in Germany, ""hipster hate"" in German political discourse or the politics of expertise and anti-elite iconography in high fashion internationally. The book is intended for undergraduates, postgraduates and postdoctoral researchers.